Analisis Peran Indonesia dalam Kerjasama Keamanan Trilateral di Laut Sulawesi – Sulu Pada Tahun 2016 – 2018 - Uswatun Khasanah; Tri Cahya Utama; Muhammad Faizal Alfian (Journal of International Relations Diponegoro, 2021)
In 2016 kidnappings for ransom by the Abu Sayyaf terrorist group in Sulu Sea has increased. The Indonesian government initiate to form a trilateral cooperation with the Philippines and Malaysia. In addition, Indonesia is also strive for the Hot Pursuit agreement which allows other countries to enter Indonesian teritory. Meanwhile Indonesia doesn’t have a national policy regarding the Hot Pursuit scheme by warships from other countries. It can lead to potential conflicts because of the overlapping territorial waters of the three countries and the history of conflicts between countries. This study will explain the causes of Indonesia's active role in trilateral cooperation. By using cooperative security concept and foreign policy analysis the role theory of Holsti (1970) which emphasizes the concept of national roles, alter prescripts, and status in foreign policy. This research uses literature study method through analysis of books, newspapers, and publications from relevant agencies. The result is Indonesia's active role in trilateral cooperation caused by the conception of a national role in the form of Regional Leaders, alter prescriptions in commitment to agreements, and Indonesia's status as a leading actor in the Southeast Asia region.